Representações sociais e interculturalidade: um estudo documental sobre elementos provocadores e roteiros de interação do exame Celpe-Bras - Negri, Marcia Fanti (Universidade Federal de São Carlos, 2019)
This study investigated social representations of Brazil that may be present in Provoking Elements2 and Interactional Scripts of the oral part in Celpe-Bras Exam through the perspective of interculturality (KRAMSCH, 2011; BARBOSA, 2015; VIANA E PAIVA, 2017; WALSH,2010; CANDAU,2010; FLEURI,2003). Furthermore, the analysis and interpretation of representations in this research aim to shed light on possible suggestions for the process of teaching Portuguese as a Foreign Language (PFL), considering washback effect (SCARAMUCCI, 1995, 1999; and MOUTINHO, 2006) as pivotal. The grounding theory that supports the analysis and discussion is the Theory of Social Representations (MOSCOVICI, 2015, 1988; JODELET, 2008; MARKOVÁ, 2017) in convergence of theories of interculturality and interaction (GOFFMAN, 1967; DUNCAN & FISKE,2015; LEFFA, 2006; ELLIS, 1984; MCNAMARA & ROEVER, 2010; MOSCOVICI, 2015). Methodology-wise, this study is characterized as interpretative documentary (SCOTT, 1990; LE GOFF, 1996; BAILEY, 2008) under the paradigm of qualitative research. The temporal corpus snippet revealed that few provoking elements conveyed social representations of Brazil and/or Brazilian people, or somehow favored the articulation of social representations through the interactional script. Mostly, provoking elements and interaction scripts showed representations of Brazil and/or Brazilian people that referred to potential generalizations regarding Brazil(ians). Moreover, seldom did the questions in the interactional script seem to guide the discussion through an intercultural perspective. Finally, the discussion of social representations of Brazil under the perspective of interculturality favored reflection upon the learning and teaching processes, considering its dimensions of material production, evaluation, as well as PFL teacher education and public policies for the area.
Social representations and interculturality: a documentary research on "elementos provocadores" and "roteiros de interação" of the Celpe-Bras exam
Keywords: Interculturalidade; Português língua estrangeira; Representações sociais; Interação; Interculturality; Portuguese as foreign language; Social representations; Interaction; Celpe-Bras; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::LINGUISTICA APLICADA